história de mulheres: da oralidade à cena - Miranda, Cláudia Cristina (2019)
In this research I seek to share the process of creating of V (ENTRE), the scenic material that was created from the memory of women for an in - depth investigation of a material beyond the non - fictional, autobiographical. The memory, in this case, is our subject matter of approach for creation, starting principally from the feminine that brought up us, stories that mothers and grandmothers told us and how these stories reverberate in our acting in the world. In this way, the research is based on the creation of fields that constitute the scene: body and dramaturgy, which always arise from the development of improvisational research. In the body, the improvisation arrives principally from the study of Ideokinesis and the Viewpoints, the touch in the bone that boosts the memories stored in our body, and from this stimulus create, at stake, possibilities of communication. The dramaturgy is based on the memories brought by the body and the dialogues during the rehearsals, the stories, memories and perceptions shared after the experience of the touch practiced during the corporal practice. Another thread that leads to this weaving of V (ENTRE) is playing with the gaps created in our memories, the stories of two sisters can merge, confuse or complement each other, in order to spin affections, encounters or disagreements. More than that, create a space - time of impacts generated from the scenic rewriting of the memories of two actresses. What matters in this process is the scenic investigation of the implicit re-creation in the act of remembering, of the foreign experience embodied as own memory and of the non-linear organization of such mechanism.